2011
DOI: 10.1016/j.bcp.2011.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of bupropion by baboon hepatic and placental microsomes

Abstract: The aim of this investigation was to determine the biotransformation of bupropion by baboon hepatic and placental microsomes, identify the enzyme(s) catalyzing the reaction(s) and determine its kinetics. Bupropion was metabolized by baboon hepatic and placental microsomes to hydroxybupropion (OH-BUP), threo- (TB) and erythrohydrobupropion (EB). OH-bupropion was the major metabolite formed by hepatic microsomes (Km 36 ± 6 µM, Vmax 258 ± 32 pmol mg protein−1 min−1), however the formation of OH-BUP by placental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
(33 reference statements)
2
13
0
Order By: Relevance
“…On the other hand, in human and baboon placental microsomes, the main metabolites formed were TB and EB. Furthermore, 11b-hydroxysteroid dehydrogenases were identified as the major carbonyl-reducing enzymes responsible for the reduction of BUP to TB and EB in human and baboon microsomal fractions (Wang et al, , 2011. These data support, in part, the use of baboons to study BUP disposition during pregnancy.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…On the other hand, in human and baboon placental microsomes, the main metabolites formed were TB and EB. Furthermore, 11b-hydroxysteroid dehydrogenases were identified as the major carbonyl-reducing enzymes responsible for the reduction of BUP to TB and EB in human and baboon microsomal fractions (Wang et al, , 2011. These data support, in part, the use of baboons to study BUP disposition during pregnancy.…”
Section: Introductionsupporting
confidence: 52%
“…The major metabolite determined in the baboons' plasma was OH-BUP. Previously we reported that in baboons CYP2B was the major hepatic enzyme responsible for the hydroxylation of BUP in vitro (Wang et al, 2011). Following intravenous administration of 1 mg/kg of BUP, the peak plasma concentration of OH-BUP in nonpregnant baboons was ;3-fold less than the peak level of the parent drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations